Bridging books: the printed book as a support for digital experiences - Pinto, Ana Lúcia (2013)
It has been 20 years since Pierre Wellner published the article Interacting with paper on the digital desk [1] where he challenges us to imagine a space where “Instead of replacing paper with computers we could enhance paper with computation”. Two decades after, we see the development of multiple projects that expand the expressive possibilities of traditional books by combining and crossing different media. Nevertheless the interest generated by those projects is limited, most of the time, to the research communities. The purpose of this IDC 2013 workshop is to bring together a community of researchers, publishers and authors to reflect and discuss the present and future impact of mixed media books.